1993
DOI: 10.1002/syn.890150103
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the cholinergic nature of C‐terminals associated with subsurface cisterns in α‐Motoneurons of rat

Abstract: C-terminals can be distinguished at the ultrastructural level from other types of nerve endings on motoneurons by their prominent and regularly occurring postsynaptic specializations termed subsurface cisterns (SSC). We have previously shown (Yamamoto et al., 1991) that an antibody directed against a sequence within the gap junction protein connexin32 immunolabels these motoneuronal SSCs and can therefore serve as a immunohistochemical tool to visualize indirectly the location of C-terminals on motoneurons at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
71
1
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 71 publications
(78 reference statements)
6
71
1
2
Order By: Relevance
“…8 In agreement with electron microscopy histochemical results showing high concentrations of acetylcholinesterase (AChE) reaction product at motoneuronal C-terminal subsurface cistern complexes, 10,34 a high degree of co-localization was found between immunofluorescence labelling for subsurface cisterns and AChE. 24 These results, together with our observations that large ChAT-containing boutons on motoneurons correspond to those containing AChE, suggested that most, if not all, C-terminals are cholinergic. In order to substantiate this conclusion and to confirm data derived from indirect light microscopic analyses using the antisubsurface cistern antibody, the immunohistochemical localization of the cholinergic markers ChAT and AChE in terminals on motoneurons in the facial nucleus and lumbar spinal cord of adult rats was examined by light microscopy.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…8 In agreement with electron microscopy histochemical results showing high concentrations of acetylcholinesterase (AChE) reaction product at motoneuronal C-terminal subsurface cistern complexes, 10,34 a high degree of co-localization was found between immunofluorescence labelling for subsurface cisterns and AChE. 24 These results, together with our observations that large ChAT-containing boutons on motoneurons correspond to those containing AChE, suggested that most, if not all, C-terminals are cholinergic. In order to substantiate this conclusion and to confirm data derived from indirect light microscopic analyses using the antisubsurface cistern antibody, the immunohistochemical localization of the cholinergic markers ChAT and AChE in terminals on motoneurons in the facial nucleus and lumbar spinal cord of adult rats was examined by light microscopy.…”
supporting
confidence: 85%
“…40 We found by light microscopy double immunolabelling methods that subsurface cisterns co-localize with choline acetyltransferase (ChAT)-labelled boutons on motoneurons at most cranial and spinal levels, 24 which is consistent with electron microscopic observations that C-terminals on motoneurons in the hypoglossal nucleus are cholinergic, based on their immunolabelling for ChAT. 8 In agreement with electron microscopy histochemical results showing high concentrations of acetylcholinesterase (AChE) reaction product at motoneuronal C-terminal subsurface cistern complexes, 10,34 a high degree of co-localization was found between immunofluorescence labelling for subsurface cisterns and AChE.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Early on, Conradi and Skoglund (1969) presented immunohistochemical and electronmicroscopic data revealing large terminals on spinal motoneurons. These C-boutons were later shown to be cholinergic (Nagy et al, 1993;Li et al, 1995). They were shown to develop in the early post-natal period in mice (Wilson et al, 2004) and to be in apposition to both post-synaptic type 2 muscarinic (m 2 ) receptors and delayed rectifier K V 2.1 channels (Hellström et al, 2003;Muennich and Fyffe, 2004;Wilson et al, 2004).…”
Section: Other Possible Mechanisms Of Modulation Of Motoneuron Propermentioning
confidence: 99%
“…The somata and proximal dendrites of MNs are contacted by large cholinergic varicosities named ''C boutons'' (3)(4)(5)(6)(7)(8)(9)(10)(11). It has been known since 1972 (12) that C boutons originate from spinal cord neurons, but the location of these cells remains unknown (10).…”
mentioning
confidence: 99%